Targeting dormant tuberculosis bacilli: results for molecules with a novel pyrimidone scaffold - Joshi, Rohit R.; Barchha, Avinash; Khedkar, Vijay M.; Pissurlenkar, Raghuvir R. S.; Sarkar, Sampa; Sarkar, Dhiman; Joshi, Rohini R.; Joshi, Ramesh A.; Shah, Anamik K.; Coutinho, Evans C. (Chemical Biology & Drug Design, 2015)
Our inability to completely control TB has been due in part to the presence of dormant mycobacteria. This also renders drug regimens ineffective and is the prime cause of the appearance of drug-resistant strains. In continuation of our efforts to develop novel antitubercular agents that especially target dormant mycobacteria, a set of 55 new compounds belonging to the pyrimidone class were designed on the basis of CoMFA and CoMSIA studies, and these were synthesized and subsequently tested against both the dormant and virulent BCG strain of M.tuberculosis. Some novel compounds have been identified which selectively inhibit the dormant tuberculosis bacilli with significantly low IC50 values. This study reports the second molecule after TMC-207, having the ability to inhibit tuberculosis bacilli exclusively in its dormant phase. The synthesis was accomplished by a modified multicomponent Biginelli reaction. A classification model was generated using the binary QSAR approach - recursive partitioning (RP) to identify structural characteristics related to the activity. Physicochemical, structural, topological, connectivity indices, and E-state key descriptors were used for generation of the decision tree. The decision tree could provide insights into structure-activity relationships that will guide the design of more potent inhibitors.
Keywords: Antitubercular activity; dormant tuberculosis bacilli; pyrimidones; recursive partitioning